The base of the Maastrichtian - Christensen, W; Hancock, J; Peake, N; Kennedy, W (2000)
At the Brussels Symposium on Cretaceous Stage Boundaries in 1995, the Maastrichtian Working Group decided to recommend the first occurrence of the ammonite Pachydiscus neubergicus in the Tercis quarry near Dax in the Landes, southwest France as the boundary stratotype for the base of the Maastrichtian stage. On the basis of the echinoid genus Echinocorys the Campanian- Maastrichtian boundary beds of Tercis are correlated with the succession in north Norfolk, England, which in turn is correlated with the succession at Kronsmoor, northwest Germany on the basis of belemnites and brachiopods. If the possible correlation between Tercis and northwest Germany is true, the P. neubergicus and Belemnella lanceolata standards for the base of the Maastrichtian stage are not separated by more than 0.2 m.y.